2012
DOI: 10.1007/s10103-012-1084-5
|View full text |Cite
|
Sign up to set email alerts
|

Influence of three laser wavelengths on human fibroblasts cell culture

Abstract: Although experimental studies in vitro and vivo have been numerous, the effect of laser wavelength irradiation on human fibroblast cell culture is poorly understood. This emphasizes the need of additional cellular and molecular research into laser influence with low energy and power. The aim of this study was to assess the influence of three different laser wavelengths on the human skin fibroblasts cell culture. We wanted to evaluate if near infrared lasers had any influence in healing of wounds by stimulating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 27 publications
1
15
0
4
Order By: Relevance
“…Apart from energy density, studies also focused on the influence of different wavelength on fibroblast proliferation. Crisan et al (14) compared the effects of 830, 980, and 2,940 nm lasers (5.5 J/cm 2 ) on human skin fibroblasts by MTT assay and apoptosis assay. They demonstrated that both 830 and 980 nm significantly stimulated cell proliferation at 24, 48, 72 h post-irradiation but 2,940 nm inhibited cell proliferation and promoted apoptosis.…”
Section: Proliferation and Differentiationmentioning
confidence: 99%
“…Apart from energy density, studies also focused on the influence of different wavelength on fibroblast proliferation. Crisan et al (14) compared the effects of 830, 980, and 2,940 nm lasers (5.5 J/cm 2 ) on human skin fibroblasts by MTT assay and apoptosis assay. They demonstrated that both 830 and 980 nm significantly stimulated cell proliferation at 24, 48, 72 h post-irradiation but 2,940 nm inhibited cell proliferation and promoted apoptosis.…”
Section: Proliferation and Differentiationmentioning
confidence: 99%
“…It is difficult to compare our results with observations of other studies in the literature, because most studies have reported only one or two different single wavelength and treatment design varies depending on individual studies [10,11]. However, some studies have been performed in a similar manner to our study [12,20,21]. Bogdan Crisan has compared near-infrared laser light at wavelength of 830 nm, 980 nm, and 2,940 nm.…”
Section: Discussionmentioning
confidence: 88%
“…It has been reported that 780 nm laser light can up-regulate the production of basic fibroblastic growth factor (bFGF) more than 660 nm visible red laser [12]. Diabetic fibroblasts irradiated at 830 nm have shown more bFGF release compared to those irradiated at 632.8 nm [20].…”
Section: Discussionmentioning
confidence: 99%
“…Experimental in vitro studies conducted by our research team in recent years related to laser radiation effects on human fibroblasts involved in healing and tissue regeneration processes [ 13 , 14 ] enabled us to develop new protocols of irradiation on other human cell types such as osteoblasts.…”
Section: Background and Aimsmentioning
confidence: 99%